2019
DOI: 10.1016/j.ajpath.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Disordered Degradation of Neutrophil Extracellular Traps in Necrotizing Lesions of Anti-Neutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is characterized by the production of ANCAs and systemic necrotizing vasculitis in small vessels. Disordered regulation of neutrophil extracellular traps (NETs) is critically involved in the pathogenesis of AAV. NETs are web-like DNA decorated with antimicrobial proteins; they are extruded from activated neutrophils. The principal degradation factor of NETs in vivo is DNase I; however, NETs resistant to DNase I can persist in tissues and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Analysis of NETs showed weaker degradation of extracellular DNA in eosinophylic granulomatosis with polyangiitis associated with SLE patients. This phenomenon appears to be a characteristic of autoimmune disease (30,31). DNase I was inhibited by complement over-activation as well as excessive deposition of the complement protein, C1q, which resulted in the inability to degrade NETs (13).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of NETs showed weaker degradation of extracellular DNA in eosinophylic granulomatosis with polyangiitis associated with SLE patients. This phenomenon appears to be a characteristic of autoimmune disease (30,31). DNase I was inhibited by complement over-activation as well as excessive deposition of the complement protein, C1q, which resulted in the inability to degrade NETs (13).…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 11, 2021. ; https://doi.org/10.1101/2021.02.09.430558 doi: bioRxiv preprint and necrotizing granulomas (10). Generation of the NETs in necrotizing granulomas of pulmonary tuberculosis could be mediated by the abilities of immune complexes to induce NET release in neutrophils (8).…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing granuloma is a hallmark of pulmonary tuberculosis and is shown to have abundant NETs (10). Abundant NETs have also been reported in necrotizing granulomas from patients with granulomatosis with polyangiitis, a small vessel vasculitis condition in which neutrophils and NETs were associated with necrosis of blood vessels and necrotizing granulomas (10). Generation of the NETs in necrotizing granulomas of pulmonary tuberculosis could be mediated by the abilities of immune complexes to induce NET release in neutrophils (8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed that ANCA antibodies are not only a biomarker of AAV but are involved in the pathogenesis of the renal involvement in AAV. Binding of MPO or proteinase 3 antibodies to autoantigens activates neutrophils, that degranulate and release reactive oxygen species [11]. Neutrophil extracellular traps (NETs) are released to contain infections, but if they are not properly regulated, they damage the endothelium and activate complement, thus provoking inflammation and microvascular thrombosis, explained as ANCA-cytokine sequence theory [12], [13].…”
Section: Discussionmentioning
confidence: 99%